Blockchain Implementation Quality Challenges: A Literature Review - Koteska, Bojana; Karafiloski, Elena; Mishev, Anastas (CEUR-WS.org, 2017)
Blockchain is a public digital and distributed database solution providing decentralized management of transaction data. Since the introduction of Bitcoin cryptocurrency, which was the first implementation of the Blockchain technology in 2008, the interest in Blockchain technology has been constantly increasing. Blockchain is not applicable only in financial transaction systems but it is transforming our society from the way we use our cars, smartphones, healthcare, vote, and even personal identication. As such when we discuss the Blockchain implementation we are really discussing three dierent things: Blockchain ledger, Blockchain network and clients. Modern Blockchain implementations have to adapt to some technical challenges and limitations required for Blockchain technology. For example, security, privacy, throughput, size and bandwidth, performance, usability, data integrity and scalability are just some of the attributes required for high quality Blockchain implementation. In this paper, we aim to analyze the current quality issues in the Blockchain implementation and to identify the Blockchain quality attributes. A literature review is conducted to investigate the current quality requirements for Blockchain implementation. Findings show that the research on quality requirements for Blockchain implementation is still in its early stage. The conclusions of this study could be used for further analysis of the quality attributes required for the Blockchain implementations and improvement of the quality of the Blockchain systems.